Prevalence and determinants of smoking behavior among physicians in emergency department: A national cross-sectional study in China - Zong, Qiao; Li, Hui; Jiang, Nan; Gong, Yanhong; Zheng, Jianwei; Yin, Xiaoxv (Frontiers in Public Health, 2022)
Abstract Objectives To understand the current status of smoking behavior among emergency physicians in China and to explore its determinants. Background The emergency department is considered a more appropriate setting for tobacco interventions. However, the smoking behavior of emergency physicians can reduce the effectiveness of interventions for patient smoking behavior. Methods From July to August 2018, we conducted a structured online questionnaire among Chinese emergency medicine physicians. We used descriptive analysis with binary logistic regression to analyze the current smoking status of Chinese emergency physicians and its determinants. Results A total of 10,457 emergency physicians were included in this study. The prevalence of smoking among physicians was 25.35% (with 34.15% and 1.59% among male and female physicians, respectively). Results of logistic regression showed that postgraduate education (OR = 0.52, 95% CI: 0.41-0.66), chief-level title (OR = 0.79, 95% CI: 0.65-0.97), and regular exercise habits (OR = 0.83, 95% CI : 0.76-0.92) were associated with a lower risk of smoking behavior. However, being over 50 years old (OR = 1.71, 95%CI : 1.29-2.27), being fixed-term (OR = 1.25, 95%CI : 1.10-1.42), and having depressive symptoms (OR = 1.43, 95%CI : 1.28-1.61) were associated with a higher risk of smoking. Conclusion The prevalence of smoking behavior among emergency physicians in China is high. Hospital management could reduce the incidence of smoking behavior among emergency physicians by strengthening smoking cessation training, paying attention to physicians' psychological health, reducing pressure on physicians in fixed-term positions, and encouraging physicians to develop regular exercise habits.